2020
DOI: 10.1038/s41598-020-62804-3
|View full text |Cite
|
Sign up to set email alerts
|

Attractor Concepts to Evaluate the Transcriptome-wide Dynamics Guiding Anaerobic to Aerobic State Transition in Escherichia coli

Abstract: For any dynamical system, like living organisms, an attractor state is a set of variables or mechanisms that converge towards a stable system behavior despite a wide variety of initial conditions. Here, using multi-dimensional statistics, we investigate the global gene expression attractor mechanisms shaping anaerobic to aerobic state transition (AAT) of Escherichia coli in a bioreactor at early times. Out of 3,389 RNA-Seq expression changes over time, we identified 100 sharply changing genes that are key for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…For studying Toll-like receptor induced immune response, the correlation metrics revealed that immune-related local genes were highly responsive while myriad global genes showed significantly less response 21,22 . In a similar way, for E. coli, we showed the subset of attractor genes, crucial for cell state transition, showed the most pronounced correlation metrics, while the rest of transcriptome lacked significance 23 . The PC metrics revealed that the attractor genes tracked almost identical trajectory compared with the transcriptome-wide response 23 .…”
Section: Correlation and Pca Shows Significant Response Of De Genes supporting
confidence: 62%
See 2 more Smart Citations
“…For studying Toll-like receptor induced immune response, the correlation metrics revealed that immune-related local genes were highly responsive while myriad global genes showed significantly less response 21,22 . In a similar way, for E. coli, we showed the subset of attractor genes, crucial for cell state transition, showed the most pronounced correlation metrics, while the rest of transcriptome lacked significance 23 . The PC metrics revealed that the attractor genes tracked almost identical trajectory compared with the transcriptome-wide response 23 .…”
Section: Correlation and Pca Shows Significant Response Of De Genes supporting
confidence: 62%
“…In a similar way, for E. coli, we showed the subset of attractor genes, crucial for cell state transition, showed the most pronounced correlation metrics, while the rest of transcriptome lacked significance 23 . The PC metrics revealed that the attractor genes tracked almost identical trajectory compared with the transcriptome-wide response 23 . These data revealed that both correlation and PC metrics can be used to test the significance of Scatlay-derived DE genes.…”
Section: Correlation and Pca Shows Significant Response Of De Genes supporting
confidence: 62%
See 1 more Smart Citation
“…Previous studies have revealed that during the switch from anaerobiosis to aerobiosis and vice versa, E. coli reprograms gene expression to adjust its cellular metabolism, energy production, and iron homeostasis. Recently, several studies have analyzed the impact of oxygen availability on genome-wide expression profiles, focusing on specific regulatory systems or changes associated with aerobic-anaerobic transitions in E. coli [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Dimensionality reduction techniques, such as SVD used here and generalized SVD for multi-omic and pan-cancer studies, have proven useful because they represent the information of the entire system as linear combinations of orthogonal basis vectors [2][3][4] . Similar mathematical approaches including endogenous network theory have been used to identify steady states, or attractors, using configurations of gene regulatory networks [5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%